2011
DOI: 10.1007/s12603-011-0003-y
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritional approach for inhibiting bone resorption in institutionalized elderly women with vitamin D insufficiency and high prevalence of fracture

Abstract: abstract:Background: nutritional approach to the deterioration of bone integrity and increased fracture risk appears to be particularly appropriate in elderly women living in nursing homes. Objective: to investigate the beneficial effect of the consumption of soft plain cheese on bone resorption markers in institutionalized elderly women. Design: Prospective, randomized crossover controlled study. Setting: six French nursing homes or other institutions for elderly. Participants: institutionalized women ≥ 65 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Many reports relating to the intake of these nutrients have emphasised their importance in the prevention of bone loss and thus in the reduction of the risk of fractures in the elderly (94). Being a source of calcium and protein, dairy products could play a positive role on bone health (42).…”
Section: Mineral Saltsmentioning
confidence: 99%
“…Many reports relating to the intake of these nutrients have emphasised their importance in the prevention of bone loss and thus in the reduction of the risk of fractures in the elderly (94). Being a source of calcium and protein, dairy products could play a positive role on bone health (42).…”
Section: Mineral Saltsmentioning
confidence: 99%
“…Two French studies have evaluated the effects of 2 daily servings of calcium-and vitamin D-fortified soft cheese providing a daily dose of 400 mg of calcium, 2.5 mcg (100 IU) of vitamin D 3, and 13.8 g of protein vs usual diet [13,14]. One of the studies was conducted in older institutionalized women mean age 87±6 years with hypovitaminosis D and calcium intake below 700 mg/day.…”
Section: Calciummentioning
confidence: 99%
“…One of the studies was conducted in older institutionalized women mean age 87±6 years with hypovitaminosis D and calcium intake below 700 mg/day. After 6 weeks, there were significant increases in 25-hydroxyvitamin D levels, higher levels of serum insulin-like growth factor-I (IGF-I), a bone anabolic factor, and significant reductions in 2 markers of osteoclast activity and bone resorption, bone specific acid phosphatase tartrate resistant acid phosphatase isoform 5b (TRAP 5b), and serum carboxy-terminal cross-linked telopeptide of type I bone collagen (CTX) [13]. The same intervention was tested in younger women, mean age 56±3.9 years, who were, on average, within 7.5 years from menopause and had calcium intake below 650 mg/day [14].…”
Section: Calciummentioning
confidence: 99%
“…According to the study, the association of these with the lack of sun exposure may increase the risk of fractures by increasing bone loss and the propensity for falls. 16 In addition to this, recent studies have shown that vitamin D deficiency is related to other pathologies such as cancer, diabetes melittus 17 and cardiovascular processes, such as hypertension and atherosclerosis. 18 Observational studies demonstrate such associations, but interventional studies, for the most part, fail to demonstrate the benefit of reducing such outcomes.…”
Section: Discussionmentioning
confidence: 98%